World Allergy Organization (WAO) Diagnosis and Rationale for Action against Cow's Milk Allergy (DRACMA) Guideline update – VII – Milk elimination and reintroduction in the diagnostic process of cow's milk allergy - Rosan Meyer, RD, PhD; Carina Venter, RD, PhD; Antonio Bognanni, MD, PhD(s); Hania Szajewska, MD, PhD; Raanan Shamir, MD, PhD; Anna Nowak-Wegrzyn, MD, PhD; Alessandro Fiocchi, MD, PhD; Yvan Vandenplas, MD, PhD (World Allergy Organization Journal, 2023)
The diagnosis of cow's milk allergy (CMA) in infants and young children remains a challenge because many of the presenting symptoms are similar to those experienced in other diagnoses. Both over- and under-diagnosis occur frequently. Misdiagnosis carries allergic and nutritional risks, including acute reactions, growth faltering, micronutrient deficiencies and a diminished quality of life for infants and caregivers. An inappropriate diagnosis may also add a financial burden on families and on the healthcare system.Elimination and reintroduction of cow's milk (CM) and its derivatives is essential for diagnosing CMA as well as inducing tolerance to CM. In non-IgE mediated CMA, the diagnostic elimination diet typically requires 2–4 weeks before reintroduction, while for IgE mediated allergy the time window may be shorter (1–2 weeks). An oral food challenge (OFC) under medical supervision remains the most reliable diagnostic method for IgE mediated and more severe types of non-IgE mediated CMA such as food protein induced enterocolitis syndrome (FPIES). Conversely, for other forms of non-IgE mediated CMA, reintroduction can be performed at home. The OFC cannot be replaced by the milk ladder after a diagnostic elimination diet. The duration of the therapeutic elimination diet, once a diagnosis was confirmed, can only be established through testing changes in sensitization status, OFCs or home reintroduction, which are directed by local protocols and services' availability. Prior non-evidence-based recommendations suggest that the first therapeutic elimination diet should last for at least 6 months or up to the age of 9–12 months, whichever is reached first. After a therapeutic elimination diet, a milk-ladder approach can be used for non-IgE mediated allergies to determine tolerance. Whilst some centers use the milk ladder also for IgE mediated allergies, there are concerns about the risk of having immediate-type reactions at home. Milk ladders have been adapted to local dietary habits, and typically start with small amounts of baked milk which then step up in the ladder to less heated and fermented foods, increasing the allergenicity.This publication aims to narratively review the risks associated with under- and over-diagnosis of CMA, therefore stressing the necessity of an appropriate diagnosis and management.